Marketplace Accountability Regulatory Model for the Online Distribution of Hard Drugs (Prescription Drugs) - Putri Purbasari Raharningtyas Marditia; Putu Devi Kuaumawardani (Universitas Katolik Soegijapranata Semarang, 2022)
Abstract : A marketplace is a platform that provides and sells various kinds of commodity goods ranging from daily necessities to medicines. Marketplace users come from ages ranging from teenagers to adults, so problems arise for those who are not yet adults and make online transactions through this platform. In this paper, the author wants to discuss how the marketplace is responsible for selling drugs, one of which is abortion drugs that can be purchased freely, including by people who are not yet adults. The writing methodology used by the author is normative juridical based on library research using secondary data, namely legislation and law books. A license to sell drugs is required under the applicable laws and regulations to avoid unlawful acts and harm to consumers. Furthermore, the marketplace party should run a checking and filtering system for selling medicinal commodities to prevent illegal actions and losses. Some drugs need a prescription and are forbidden to be sold freely.. Keywords: Regulation, Marketplace, Drug Circulation, Online Transaction Abstrak: Marketplace adalah wadah atau platform yang menyediakan dan menjual berbagai macam barang komoditas mulai dari kebutuhan sehari-hari hingga obat-obatan. Pengguna marketplace berasal dari kalangan usia mulai dari remaja hingga usia dewasa, sehingga timbul permasalahan bagi mereka yang belum dewasa dan melakukan transaksi online melalui platform marketplace ini. Dalam paper ini, Penulis ingin membahas bagaimana pertanggungjawaban marketplace terhadap penjualan obat-obatan salah satunya obat aborsi yang dapat dibeli secara bebas, termasuk oleh orang yang belum dewasa. Metodologi penulisan yang digunakan penulis adalah yuridis normatif berdasarkan penelitian keperpustakaan dengan jenis data sekunder, yaitu perundang-undangan, buku-buku, literatur, dan kamus. Untuk menghindari perbuatan melawan hukum dan kerugian bagi konsumen, dibutuhkan ijin penjualan obat-obatan sesuai dengan peraturan perundang-undangan yang berlaku. Untuk mengindari perbuatan melawan hukum dan kerugian, pihak marketplace sepatutnya harus menjalankan sistem pengecekan dan pemfilteran terhadap komoditas obat-obatan yang boleh atau tidak boleh dijual secara bebas.Kata Kunci : Peraturan, Marketplace, Peredaran Obat, Transaksi Online